Post-hoc analyses of the edaravone clinical trials Study 16 and Study 19: a step toward more efficient clinical trial designs in amyotrophic lateral sclerosis. Issue 5 (3rd July 2019) - Palumbo, Joseph M.; Hubble, Jean; Apple, Stephen; Takei, Koji; Tsuda, Kikumi; Liu, Shawn; Zhang, Jeffrey; Agnese, Wendy
Abstract: Objectives: The edaravone development program established a study design in which a treatment effect slowing functional loss in amyotrophic lateral sclerosis (ALS) could be documented within a 24-week time frame. This report elucidates the strategic enrichment design utilized to create efficiency and precision in the development program. Methods: Post-hoc analyses describe learning, sequential iteration, and evolution in study design. Results: The first Phase 3 study of edaravone in ALS (Study MCI186-16) included a large proportion (35%) of placebo patients who were minimal progressors. These patients demonstrated high heterogeneity in change in ALSFRS-R score (−4 median with interquartile range [IQR] 7.5) and a modal distribution score of 0, suggesting evidence of minimal change in ALSFRS-R during the study. This level of variability and rate of progression may have made it difficult to detect a prospective treatment effect in the study. A strategic enrichment strategy provided the second Phase 3 study (Study MCI186-19) with the ability to detect a treatment effect. In Study MCI186-19, only 13% of the placebo patients were minimal progressors. Further, these placebo patients demonstrated less heterogeneity and greater functional progression of ALS, thereby providing greater likelihood of detecting a treatment effect. The enrichment strategy may have excluded some rapidly progressing patients, potentially supporting the detection of a treatment effect. As previously published, Study MCI186-19 prospectively documented a 33% reduction in rate of progression of ALS ( p = 0.0013). Conclusions: Strategic choices in the design of Study MCI186-19 reduced the proportion of minimally progressing patients and supported detection of a treatment effect.